2017
DOI: 10.1016/j.jgeb.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial nitric oxide synthase gene (T786C and G894T) polymorphisms in Egyptian patients with type 2 diabetes

Abstract: BackgroundGenetic factors play important role in the development of type 2 diabetes and diabetic nephropathy. Endothelial nitric oxide synthase (eNOS) gene is responsible for the bioavailability of nitric oxide and endothelial function.AimTo assess the association of the endothelial nitric oxide synthase (eNOS) (T786C and G894T) single nucleotide polymorphisms with Egyptian type 2 diabetes mellitus and diabetic nephropathy.Patients and methodsA total of 200 type 2 diabetic patients and 100 apparently healthy v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 31 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…Experimental evidences have suggested that levels of urea, creatinine and glucose levels are involved in increased insulin resistance and promote the progression of renal disease in T2D patients (Neumiller and Hirsch 2015 ; Kashima et al 2017 ; Li et al 2018 ; Osman et al 2018 ; Xie et al 2018 ; Zaman et al 2018 ; Davies et al 2018 ). Although there are few studies available on the association of eNOS and MCP-1 genotypes with T2D and DN phenotypes, these studies have not deciphered the association of these genotypes with BMI, urea, creatinine and random blood sugar levels (Joo et al 2007 ; Hassan et al 2010 ; Moguib et al 2017 ; Sadati et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidences have suggested that levels of urea, creatinine and glucose levels are involved in increased insulin resistance and promote the progression of renal disease in T2D patients (Neumiller and Hirsch 2015 ; Kashima et al 2017 ; Li et al 2018 ; Osman et al 2018 ; Xie et al 2018 ; Zaman et al 2018 ; Davies et al 2018 ). Although there are few studies available on the association of eNOS and MCP-1 genotypes with T2D and DN phenotypes, these studies have not deciphered the association of these genotypes with BMI, urea, creatinine and random blood sugar levels (Joo et al 2007 ; Hassan et al 2010 ; Moguib et al 2017 ; Sadati et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Giusti et al, eNOS T-786C gene polymorphism was found to be associated with a decrease in eNOS gene promoter activity. Furthermore, in the same study, this polymorphism was found to be an independent risk factor for plasma homocysteine concentrations [7][8][9]. It is presented primer sequences that used to determine eNOS T-786, G894T, Intron 4a/4b gene polymorphisms in Table 3.…”
Section: Forward Primer 5′-3′mentioning
confidence: 96%
“…The eNOS 4a or 894 T allele increased DN progression in a sample of Iranian T2DM cases [ 291 ]. The correlation of type 2 diabetes with TT genotype of eNOS G894T variant was also found among a sample of Egyptian cases [ 292 ]. End-stage renal disease (ESRD) is mainly caused by DN.…”
Section: Introductionmentioning
confidence: 99%